Exploring the Impact of Coping Stress on Enhancing Employees' Overall Quality of Work Life - H.D. Sitorus, Friyanka; Ernawati Tamba, Maria; Noviolarosa Panjaitan, Sarah; Hartini, Sri; Silviana Nainggolan, Rotua (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
The increase in employee work stress due to changes in the modern workplace has affected employee well-being and quality of work life. This study aims to analyze the relationship between stress coping and employees’ quality of work life and to identify the existence of a significant positive relationship between the two variables. This study uses a quantitative approach involving 200 employees from a Suzuya branch in Medan, with a Likert scale used to measure coping stress and quality of work life. The results indicate a significant positive relationship between coping stress and quality of work life, where workplace stress and social support significantly impact employee well-being, while time management does not show a significant influence. These findings suggest that organizations need to prioritize stress management initiatives and strengthen social support systems to improve employee quality of work life, which in turn can contribute to job satisfaction and productivity. By creating a supportive work environment, organizations can foster greater engagement and performance, leading to overall organizational success.